Innate Immunity of Plants, Animals, and Humans - Heine, Holger. (Springer, 2017)
Evolution of resistance genes in plants /|rShunyuan Xiao, Wenming Wang, Xiaohua Yang --|tThe path less explored: innate immune reactions in Cnidarians /|rThomas C.G. Bosch --|tBug versus bug : humoral immune responses in Drosophila melanogaster /|rDeniz Ertürk-Hasdemir [and others] --|tCellular immune responses in Drosophila melanogaster /|rAdrienne Ivory, Katherine Randle, Louisa Wu --|tImmune reactions in the vertebrates' closest relatives, the urochordates /|rKonstantin Khalturin, Ulrich Kürn, Thomas C.G. Bosch --|tInnate immune system of the zebrafish, Danio rerio /|rCon Sullivan, Carol H. Kim --|tToll-like receptors in the mammalian innate immune system /|rAndrei E. Medvedev, Stefanie N. Vogel --|tNLRs : a cytosolic armory of microbial sensors linked to human diseases /|rMathias Chamaillard --|tAntimicrobial peptides as first-line effector molecules of the human innate immune system /|rRegine Gläser, Jürgen Harder, Jens-Michael Schröder --|tThe complement system in innate immunity /|rK.R. Mayilyan [and others].